1998
DOI: 10.1007/s003810050240
|View full text |Cite
|
Sign up to set email alerts
|

A case of Rathke's cleft cyst with apoplexy

Abstract: We report a case of Rathke's cleft cyst associated with cholesterin granuloma in an 8-year-old girl with apoplexy. She was admitted to our hospital in April 1996 because of repeated headache and deep ophthalmic pain, without any visual disturbance. Computed tomography (CT) of the pituitary demonstrated an intrasellar isodense mass extending to the suprasellar cistern. Magnetic resonance imaging (MRI) showed a high-intensity mass on both T1- and T2-weighted images. The preoperative diagnosis of this lesion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…7) Only 13 cases of RCC with granulomatous change have been diagnosed by pathological examination (Table 1). 1,[4][5][6][8][9][10][11][12][13]16,18,20) Four cases showed xanthogranulomatous change (Cases 3, 4, 6, and 8) and 2 cases had ossification of the cyst wall (Cases 6 and 8). Another case of ossifying xanthogranuloma in the dermis was described as being secondary to a metaplastic process.…”
Section: Discussionmentioning
confidence: 99%
“…7) Only 13 cases of RCC with granulomatous change have been diagnosed by pathological examination (Table 1). 1,[4][5][6][8][9][10][11][12][13]16,18,20) Four cases showed xanthogranulomatous change (Cases 3, 4, 6, and 8) and 2 cases had ossification of the cyst wall (Cases 6 and 8). Another case of ossifying xanthogranuloma in the dermis was described as being secondary to a metaplastic process.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of a hemorrhagic suprasellar mass includes Rathke cleft cyst [1][2][3][4], craniopharyngioma [5,6], optic or hypothalamic glioma [7][8][9][10][11][12], cavernous angioma [13], venous angioma [14,15], germinoma [16], meningioma [17][18][19], and aneurysm. We describe the first reported case of pituicytoma presenting with spontaneous hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports of RCCs presenting with apoplexy all described intracystic hemorrhage seen at the time of surgery. 11,12 In the case series by Binning et al, preoperative MR imaging also demonstrated mixed signal intensities suggestive of hemorrhagic pituitary tumor, which intraoperatively was found to be the intracystic nodule of the RCC. Because intracystic hemorrhages have also been noted within RCCs, the diagnosis becomes even more difficult.…”
Section: Discussionmentioning
confidence: 99%